Alkali-activated waste ceramics: Importance of precursor particle size distribution. Issue 22 (15th November 2021) - Pommer, Vojtěch; Vejmelková, Eva; Černý, Robert; Keppert, Martin
Abstract: The waste ceramics belongs to wide range of aluminosilicate materials which can be alkaline-activated to geopolymer cement – possible "green" alternative to conventional Portland cement. The studied ceramic material is generated during the size adjustment of ceramic building blocks by means of grinding. It means that most of the material is very fine, but it contains also some larger shards. This ceramic powder was used as geopolymer precursor "as received" and after removal of particles retained on 1, 0.5 and 0.125 mm sieves. These four types of precursor were activated by sodium silicate (SiO2 /Na2 O = 1) solution. The prepared mortars were tested for strength, basic physical properties, transport parameters and characterized by help of XRD and thermal analysis. It was found that the best mechanical performance provided the precursor after removal of particles retained on 0.5 mm sieve thanks to the highest geopolymerization rate. The presence of coarser particles in precursor gave rise to porosity, what consequently influenced transport parameter of geopolymers towards the lower thermal conductivity and faster moisture transport. Highlights: Influence of ceramic precursor granulometry on geopolymer performance. Particles retained on 0.5 mm sieve are reducing the strength. Coarser precursor means higher porosity and lower thermal conductivity.